The sentinel lymph node dissection technique in breast cancer by using subdermal, periareolar injection of isotop Tc99mand blue dye - Kopacz, Andrzej; Świerblewski, Maciej; Lass, Piotr; Bandurski, Tomasz; Jastrzębski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2002)
Sentinel lymph node dissection in breast cancer is performed more and more often. The assessment of this node as metastases marker to the regional lymph node system may have impact to the limit the range of surgery in this region. The side effect of regional lymph nodes excision, which sometimes are serious, may be limited by using only sentinel diagnosis. There are many different methods of diagnosis of sentinel node - the first node between tumour and regional lymphatic system. The dye methods and isotope methods may be used. The sites of injection are different too: subdermal or peritumoral injections are used. Authors describe one of these method: subdermal injection of blue dye and isotope in subareolar region. In authors' opinion this method is the most effective, especially in internal quadrants tumor localization and Space' region. The place of injection is very important. Peritumoral injection require 3-4 points of injection and the background radiation is relatively high. When tuomors are localized to the inner quadrants near the sternum, the intradermal injection of the radiocolloid can be done on the border of the aerola. In this situation the shadowing is far enough from the internal mammary nodes. Lymphoscintygraphy is one of the most important parts of this method. This isotope diagnosis is performed one day before the operation day. In this assay we can locate sentinel node not only in axillary region but into internal mammary nodes or subclavian nodes too. By lymphoscintygraphy the localization of the sentinel on the skin of the axilla is possible. Intraoperativly two methods of sentinel identyfication are performed - dye and isotope. These methods are suplementary and the false negative rates are minimal at this way of identyfication. The isotope method may help identyficate the true sentinel between a few dye coloured nodes. The isotope technique of sentinel identyfication is peformed with using hand-hold gamma detector (NeoProbe). In authors opinion this suplementary methods of sentinel node identyfication is the most effective. The lerning curve is minimal and more short than in only dye or isotope method.